2020
DOI: 10.1186/s12862-019-1562-5
|View full text |Cite
|
Sign up to set email alerts
|

How long do Red Queen dynamics survive under genetic drift? A comparative analysis of evolutionary and eco-evolutionary models

Abstract: Background: Red Queen dynamics are defined as long term co-evolutionary dynamics, often with oscillations of genotype abundances driven by fluctuating selection in host-parasite systems. Much of our current understanding of these dynamics is based on theoretical concepts explored in mathematical models that are mostly (i) deterministic, inferring an infinite population size and (ii) evolutionary, thus ecological interactions that change population sizes are excluded. Here, we recall the different mathematical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 82 publications
0
24
0
Order By: Relevance
“…The fixation probability, mean extinction time, and stationary distribution are accessible by the same means as for the continuum limit. Applications of diffusion approximations are abundant and cover diverse topics (e.g., Assaf & Mobilia, 2011;Constable et al, 2016;Czuppon & Gokhale, 2018;Czuppon & Traulsen, 2018;Débarre & Otto, 2016;Houchmandzadeh, 2015;Kang & Park, 2017;Koopmann et al, 2017;McLeod & Day, 2019;Parsons et al, 2018;Reichenbach et al, 2007;Schenk et al, 2020;Serrao & Täuber, 2017;Traulsen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The fixation probability, mean extinction time, and stationary distribution are accessible by the same means as for the continuum limit. Applications of diffusion approximations are abundant and cover diverse topics (e.g., Assaf & Mobilia, 2011;Constable et al, 2016;Czuppon & Gokhale, 2018;Czuppon & Traulsen, 2018;Débarre & Otto, 2016;Houchmandzadeh, 2015;Kang & Park, 2017;Koopmann et al, 2017;McLeod & Day, 2019;Parsons et al, 2018;Reichenbach et al, 2007;Schenk et al, 2020;Serrao & Täuber, 2017;Traulsen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, large populations have a higher evolutionary potential than populations of finite size or subjected to bottlenecks, which are constrained by low genetic diversity and genetic drift [14]. Theoretical studies demonstrated that population size can change the rate of reciprocal adaptation [15], shift the outcome of antagonistic interactions in favour of the antagonist with a larger population size [16] and produce qualitatively distinct coevolutionary dynamics [17][18][19]. However, empirical evidence for these effects is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…This speaks to an important question, is the new strain here to stay or is it too transmissible for its own good?—as hinted at by considerations from evolutionary virology (Ignacio-Espinoza, Ahlgren, & Fuhrman, 2020; Peng et al, 2017; Schenk, Schulenburg, & Traulsen, 2020; Woods et al, 2011). In principle, this question can be addressed using model comparison, when the course of the epidemic reveals itself over the next month or two.…”
Section: Resultsmentioning
confidence: 99%